Umbilical Artery Doppler Flow Velocimetry in IUGR And its Relation to Perinatal Outcome - Qureshi, Faryal; Muhammad Nafees; Javaid, Aamna; Taqi, Irum; Bukhari, Fawad Gohar (Indus Journal of Bioscience Research, 2025)
Background: Intrauterine growth restriction (IUGR) is one of the leading causes of perinatal morbidity and mortality, and it is mostly caused by placental insufficiency. Umbilical artery (UA) Doppler velocimetry is a non-invasive tool used to determine fetoplacental circulation and identify fetuses who are at risk of poor outcomes. Objectives of this study are to 1) determine the frequency of abnormal umbilical artery Doppler velocimetry in pregnancies complicated by IUGR and 2) evaluate the frequency of perinatal outcomes in the cases with abnormal Doppler findings. Material and Methods: This hospital-based descriptive cross-sectional study was carried out on 149 pregnant women with the diagnosis of IUGR with a gestational age of at least 28 weeks. Umbilical artery Doppler examination was done for the categorization into normal and abnormal. Patients were followed up till delivery and perinatal outcomes such as mode of delivery, low birth weight, preterm birth, Apgar score at 5 minutes, admission to the neonatal intensive care unit and neonatal death were recorded. Data were analyzed with the help of the SPSS 25.0 and frequencies and percentages were obtained. Study confounders were controlled through stratification; chi-square and Fisher exact test was applied and p-value ≤0.05 considered as significant. Results: Abnormal umbilical artery Doppler was observed in 61 (40.9%) cases. Compared to the normal Doppler group, abnormal Doppler was significantly associated with higher rates of cesarean delivery (75.4% vs 35.2%), low Apgar score at 5 minutes (39.3% vs 14.8%), low birth weight (60.7% vs 20.5%), preterm birth (29.5% vs 4.5%), and NICU admission (80.3% vs 27.3%) (p<0.05). Neonatal death was higher in the abnormal Doppler group (6.6% vs 1.1%) but did not reach statistical significance (p=0.071). Conclusion: Abnormal umbilical artery Doppler velocimetry in IUGR is common and is highly correlated with poor perinatal outcome. Its routine use can help in the early risk stratification and better clinical decision-making and ultimately improve perinatal outcomes.